Tackling mosaicism in gene edited livestock - Salvesen, Hamish A.; Grupen, Christopher G.; McFarlane, Gus R. (Frontiers in Animal Science, 2024)
The farming of livestock has a critical role to play in global nutritional security and poverty alleviation. To meet these goals through more efficient, environmentally sustainable and animal welfare focussed means, gene editing technologies could be integrated into current breeding programs. A common issue with gene editing in livestock zygotes is the high incidence of genetic mosaicism. Genetic mosaicism, characterised by a single individual carrying distinct genotypes in different cell lineages, can lead to inconsistent presentation of a desired trait phenotypically, or the absence of the intended genotype in the animal's germline. This review explores the present status of genetic mosaicism associated with CRISPR-Cas9 gene editing in cattle, sheep, and pigs, and identifies four areas for refinement; (1) the type of CRISPR-Cas9 genome editor used; (2) the CRISPR-Cas9 formats and timing of gene editing during embryonic development;(3) the method used to deliver the genome editor and (4) the genetic screening strategies applied. We also discuss alternatives to direct zygote gene editing, including surrogate sire technology and blastomere separation, which circumvent the production of mosaic offspring. By exploring these avenues for reducing mosaicism, gene editing protocols in livestock could become more efficient and effective, which will ultimately pave the way for traits to be introduced that improve animal welfare standards and help address gaps in the security of global nutrition access.